Taxonomic studies on Scutellaria (Lamiaceae) from China (Ⅱ): the identity of S. formosana and its variety, S. formosana var. pubescens - Zeng, You-Pai; Meng, De-Chang; Zhou, Xin-Xin (Phytotaxa, 2025)
Based on critical examination of herbarium specimens (including type material) and careful observations on living plants, we demonstrate that Scutellaria formosana (Lamiaceae), previously regarded as a native of Taiwan or Hainan provinces, China, but actually from Hong Kong, and its variety, S. formosana var. pubescens, described from Hainan, are conspecific with S. stenosiphon, a species considered endemic to the Luofu Shan in Guangdong province, China, and S. javanica, a species widely distributed in Southeast Asia and China, respectively. We therefore reduce S. formosana to the synonymy of S. stenosiphon, and S. formosana var. pubescens to the synonymy of S. javanica herein. The distribution of S. stenosiphon and S. javanica in China is clarified. A distribution map of S. stenosiphon is also provided.